Effect of Various Planting Techniques and Soil Amendment on Early Growth of Selected Tree Species in Saline Soils - Kumar, G. Senthil; Ganapathy, M.; Thavaprakash, N.; Babu, C. (Indian Journal of Agroforestry, 2020)
A field experiment was carried out at Edaikal Reserve forest, Vellaiyur, Ulundurpet taluk of Tamil Nadu during the year 1998-99. The experiment consisting of different land management methods viz., Broad Bed and Furrow method (M1), Raised mound method (M2), Saucer method (M3), and Pit method (M4) with different soil amendments viz., FYM @ 12.5 t ha-1 + Gypsum @ 200 kg ha-1 + ZnSO4 @ 25 kg ha-1 + Azospirillum @ 2 kg ha-1 + Phosphobacteria @ 2 kg ha-1 (S1), Pressmud @ 15 t ha-1 + Gypsum @ 200 kg ha-1 + ZnSO4 @ 25 kg ha-1 + Azospirillum @ 2 kg ha-1 + Phosphobacteria @ 2 kg ha-1 (S2), Composted coirpith @10 t ha-1 + Gypsum @ 200 kg ha-1 + ZnSO4 @ 25 kg ha-1 + Azospirillum @ 2 kg ha-1 + Phosphobacteria @ 2 kg ha-1 (S3) and no amendments as control (S4). The results revealed that the saucer method along with FYM @ 12.5 t ha-1 + Gypsum @ 200 kg ha-1 + ZnSO4 @ 25 kg ha-1 + Azospirillum @ 2 kg ha-1 + Phosphobacteria @ 2 kg ha-1 markedly influenced the growth characters such as plant height, collar girth and root length. Among the different tree species, Leucaena leucocephala performed well in the degraded saline soils. The tree species Casuarina junghiniana and Acacia sp. were next in order. Afforestation of saline soils with species such as Leucaena leucocephala and Casuarina junghiniana holds the key role as these species have greater bioameliorative effects than others.